Aleph - Coelho, Paulo (Thorsons, 2012)
Aleph marks a return to the author's beginnings. In a frank and surprising personal story, one of the world's most beloved authors embarks on a remarkable and transformative journey of self discovery. Facing a grave crisis of faith, and seeking a path of spiritual renewal and growth, he decides to start over: to travel, to experiment, to reconnect with people and the world. On this journey through Europe, Africa, and Asia, he will again meet Hilal, the woman he loved 500 years before, an encounter that will initiate a mystical voyage through time and space, through past and present, in search of himself. Aleph is an encounter with our fears and our sins; a search for love and forgiveness, and the courage to confront the inevitable challenges of life.